Strategi Efektif dalam Kegiatan Penyusutan dan Pemeliharaan Arsip di Lembaga Kearsipan UPI - Fadilah, Syifa Diani; Silvana, Hana; Khoerunnisa, Lutfi (UI Scholars Hub, 2025)
Archives have a very important role, so an institution must have good archive management starting from archive creation to archive shrinkage. This article discusses effective efforts or strategies in archive shrinkage and archive maintenance activities at the Archival Institute of Universitas Pendidikan Indonesia (UPI). The purpose of this research is to find out the strategies or methods carried out by the institution in the depreciation and maintenance of archives. The research method in this article uses a qualitative approach and descriptive analysis of literature review, and data collection techniques are obtained through observation, interviews, and literature study. Interviews were conducted with related archivists. Overall, this research focuses on best practices that can be done in archive management to improve efficiency and effectiveness of sustainability. The strategies discussed include paying attention to the Archive Retention Schedule, the process of destroying archives is also certainly based on predetermined rules, as well as efforts to maintain physical and digital archives that have been carried out by the UPI